1999
DOI: 10.1128/mcb.19.1.515
|View full text |Cite
|
Sign up to set email alerts
|

Fiber-Type-Specific Transcription of the Troponin I Slow Gene Is Regulated by Multiple Elements

Abstract: The regulatory elements that restrict transcription of genes encoding contractile proteins specifically to either slow-or fast-twitch skeletal muscles are unknown. As an initial step towards understanding the mechanisms that generate muscle diversity during development, we have identified a 128-bp troponin I slow upstream element (SURE) and a 144-bp troponin I fast intronic element (FIRE) that confer fiber type specificity in transgenic mice (M. Nakayama et al., Mol. Cell. Biol. 16:2408-2417, 1996). SURE and F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
84
1
1

Year Published

2000
2000
2008
2008

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 81 publications
(90 citation statements)
references
References 76 publications
4
84
1
1
Order By: Relevance
“…Molkentin and coworkers (42) reported that, while CaNA␣ and CaNA␤ mutant mice exhibit a reduction of the slow/oxidative program, the effects were mediated through an NFAT-independent mechanism. Swoap et al (37) concluded from in vitro and in vivo studies that CaN and NFAT are not sufficient to dictate the slow muscle program, consistent with our previous analysis of the TnI SURE (15,27). On the other hand, McCullagh et al (36) showed that transcription from an artificially trimerized IL-2 NFAT site is selectively enhanced by slow-patterned activity, a finding we have reproduced here (Fig.…”
Section: Discussionsupporting
confidence: 80%
See 4 more Smart Citations
“…Molkentin and coworkers (42) reported that, while CaNA␣ and CaNA␤ mutant mice exhibit a reduction of the slow/oxidative program, the effects were mediated through an NFAT-independent mechanism. Swoap et al (37) concluded from in vitro and in vivo studies that CaN and NFAT are not sufficient to dictate the slow muscle program, consistent with our previous analysis of the TnI SURE (15,27). On the other hand, McCullagh et al (36) showed that transcription from an artificially trimerized IL-2 NFAT site is selectively enhanced by slow-patterned activity, a finding we have reproduced here (Fig.…”
Section: Discussionsupporting
confidence: 80%
“…S1]. Like other genes encoding contractile proteins, TnI transcription during embryonic/ early fetal development is regulated by the MRF (i.e., MyoD) and MEF-2 families of factors that bind cis elements harbored in the SURE and FIRE enhancers (21,26,27). The differential expression of TnIs and TnIf in diverse fibers is already evident during late fetal and perinatal development (15,20), but their expression becomes more confined to slow-and fast-twitch myofibers after P7 when motoneurons depolarize muscles with distinct activity patterns (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations